Enhancing Paragraph Completeness through MASS-MISS Technique in EFL Academic Writing Instruction - Ngasbun Egar; Siti Musarokah; Fitri Yulianti (ETERNAL (English Teaching Journal), 2026)
This research aims to investigate the impact of targeted instructional technique on students' paragraph writing abilities. The primary objective is to determine whether implementing Major Supporting Sentence (MASS) and Minor Supporting Sentence (MISS) techniques can significantly enhance the completeness of students' paragraph writing. The research employs a pre-experimental design, involving a one-group pre-test and post-test approach to assess the effectiveness of the treatment. Initially, students’ paragraph writing abilities were evaluated via a pre-test, which established a baseline for their competencies across various writing dimensions. The subsequent treatment, which included explicit instruction in placing MASS and MISS within paragraph writing. Post-treatment analysis revealed a significant enhancement in students' abilities to organize and articulate their thoughts in writing. The results indicated that the implementation of MASS and MISS not only improved the depth of their content but also the overall coherence and flow of their paragraphs. Statistical analysis demonstrated a substantial increase in post-test scores compared to pre-test scores, suggesting that the instructional techniques effectively addressed the weaknesses previously observed in student writing. Moreover, the effectiveness of the MASS and MISS techniques illustrates the potential for structured approaches to transform students' writing experiences